A sociotechnical framework for the design of collaborative services. (March 2018) - Baek, Joon Sang; Kim, Sojung; Pahk, Yoonyee; Manzini, Ezio
Abstract : This study was motivated by the lack of design knowledge in the area of systems design for collaborative services. It introduces a framework for developing service design goals and strategies to foster collaboration within a community, starting from an understanding of its collaboration network. Network analysis and an interview are used to understand collaboration, and a co-design workshop is used to generate design strategies to foster these relations. For validation, the framework is applied to a community enterprise in South Korea. This paper discusses: the meaning of a sociotechnical approach to collaborative service design; the challenges of co-creating sustainable solutions when empathy cannot be established with users; and the implication of the framework for service design in a sharing economy. Highlights: We propose a sociotechnical framework to support the design of collaborative services. The framework aims at developing service design goals and strategies to foster collaboration in a community. We demonstrate the framework in a case to diagnose and design for collaboration in a community enterprise in South Korea. Collaboration is assessed using network analysis and goals are formed through a co-design process. The framework is applicable to designing active participation of customers in service production.